2003
DOI: 10.1139/v03-161
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hafnium(IV) complexes in the presence of molecular nitrogen: Attempts to form dinitrogen complexes of the heaviest group 4 element

Abstract: The reaction of [P 2 N 2 ]Li 2 (dioxane) 2 with HfCl 4 (THF) 2 (where [P 2 N 2 ] = PhP(CH 2 SiMe 2 NSiMe 2 CH 2 ) 2 PPh) results in the formation of the hafnium dichloride complex [P 2 N 2 ]HfCl 2 (1). The behaviour of 1 as a potential precursor in the generation of a dinitrogen coordination complex is described. Reduction of 1 with potassium-graphite (C 8 K), under dinitrogen, under a variety of conditions led to a number of products, one of which is the dinuclear derivative with bridging P-phenyl groups that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…The longest HfeP distances were found in 5 which probably reflects the increased steric pressure from the larger alkyl groups, as well. This trend and the approximate values are reminiscent of Fryzuk's (P 2 N 2 )HfX 2 [26] and and ( Si PNP Me )HfX 3 [17,27] complexes where for X ¼ Cl, the HfeP distances (ca. 2.7 Å) were ca.…”
Section: Single Crystal X-ray Diffraction Studiesmentioning
confidence: 56%
See 1 more Smart Citation
“…The longest HfeP distances were found in 5 which probably reflects the increased steric pressure from the larger alkyl groups, as well. This trend and the approximate values are reminiscent of Fryzuk's (P 2 N 2 )HfX 2 [26] and and ( Si PNP Me )HfX 3 [17,27] complexes where for X ¼ Cl, the HfeP distances (ca. 2.7 Å) were ca.…”
Section: Single Crystal X-ray Diffraction Studiesmentioning
confidence: 56%
“…The HfeMe bond distances in Fryzuk's ( Si PNP Me )HfMe 3 [17] and (P 2 N 2 )HfMe 2 [26] are in the 2.24e2.27 Å range, and the ZreMe bond distances in our (PNP)ZrMe 3 are in the 2.25e2.29 Å range [11]. Scott and Lippard reported a series of Zr and Hf bis(trimethylsilylmethyl) complexes supported by N 4 dianionic tropocoronand ligands with MeC bonds ranging from 2.24 to 2.35 Å [21].…”
Section: Single Crystal X-ray Diffraction Studiesmentioning
confidence: 99%
“…Work with [P 2 N 2 ]Hf complexes has shown that the iodide complex can be a more productive starting material than the chloride. 33 The synthesis of [As 2 N 2 ]ZrI 2 (3) is outlined in eqn. (2).…”
Section: Methodsmentioning
confidence: 99%
“…13,52 Reductive pathways to dinitrogen complexes of hafnium have shown that the use of a diiodide precursor can give coordinated dinitrogen complexes where reduction of a dichloride species fails to do so. 33,53 If these reductions are performed in the absence of dinitrogen, phosphorus-phenyl activation occurs, giving rise to a highly activated arene bridged dimer. 54 Reduction pathways have also been used in the preparation of dinitrogen complexes of titanium.…”
Section: Group 4 Reduction Chemistrymentioning
confidence: 99%
“…The synthesis of such macrocyclic N 2 P 2 ligands is challenging, though, because it requires the control of the configuration at phosphorus. In fact, only a few P-containing macrocycles have been prepared, and N 2 P 2 macrocycles are even rarer and mostly achiral (Chart ). …”
Section: Introductionmentioning
confidence: 99%